1988
DOI: 10.1002/ar.1092200214
|View full text |Cite
|
Sign up to set email alerts
|

Lectin binding to the human retina

Abstract: Formalin-fixed, paraffin-embedded tissue sections of the human retina were stained with different fluorescein isothiocyanate-conjugated lectins. The lectins used were concanavalin A (Con A), Triticum vulgaris (WGA), glycine maximum (SBA), Dolichos biflorus (DBA), Ulex europaeus (UEA I), Arachis hypogaea (PNA), and Ricinus communis (RCA I). Con A stained both the inner and outer segments of the rods and cones, whereas WGA stained the inner and outer segments of the rods and the outer segments of the cones. PNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In addition, fluorescein isothiocyanate‐conjugated peanut ( Arachis hypogea ) agglutin (PNA; Sigma, St Louis, MO, USA) was employed to probe for the presence of cone cells at the LM level (Blanks & Johnson, 1983; Söderström, 1988; Röhlich et al ., 1989; Lukáts et al ., 2002).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, fluorescein isothiocyanate‐conjugated peanut ( Arachis hypogea ) agglutin (PNA; Sigma, St Louis, MO, USA) was employed to probe for the presence of cone cells at the LM level (Blanks & Johnson, 1983; Söderström, 1988; Röhlich et al ., 1989; Lukáts et al ., 2002).…”
Section: Methodsmentioning
confidence: 99%
“…This OX-42 antibody is suitable for pineal gland staining because the predominant type of microglia in this tissue expresses complement type 3 receptors [43]. WGA was used as a pinealocyte marker because it labels photoreceptors [44, 45], and pinealocytes are modified photoreceptor cells [46, 47]. This technique proved to be efficient in labeling these pineal cells (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…61 Their was also found in human, 40 in pig and cat and in rabbit retina. 22 These observations are different to our results.…”
Section: Articlementioning
confidence: 94%
“…40 However, there are some differences in the staining pattern of PNA and UEA-I that may result from species differences or from variation in tissue preparation, which are known to affect lectin histochemistry. 41,42 In my study, normal donkey retinal pigmented epithelium showed lectin binding sites for Con A, WGA, VVA and PNA.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation